Successful event management a practical handbook - Shone, Anton (Cengage Learning, 2010)
This work is a guide to organizing major events such as festivals, parties, concerts, weddings, and conferences. It includes photocopiable forms that will help readers to plan and budget, and case studies and websites to learn from.